Recombinant Human Adenovirus-p53 Therapy for the Treatment of Cervical Cancer: A Meta-Analysis - Guo, Yaru; Chen, Jiuzhou; Zhang, Xiwen; Fang, Miao; Xu, Mingna; Zhang, Longzhen; Rao, Enyu; Xin, Yong (Frontiers in Oncology, 2021)
Objectives: To evaluate the clinical curative effects and toxicity of recombinant human adenovirus-p53 injection (rAd-p53) plus chemotherapy (CT), radiotherapy (RT), or concurrent chemoradiotherapy (CRT) for the treatment of cervical cancer. Methods: We identified 14 eligible studies in the PubMed, Web of Science, Cochrane Library, Embase, CNKI, Wangfangdate, CBM, and VIP databases from their inception to May 2021 and performed meta-analyses using RevMan version 5.3. Results:This analysis included 14 studies involving 737 patients. The results of the meta-analysis results showed significantly improved complete remission (odds ratio [OR]=2.54, 95% confidence interval [CI]:1.74–3.70, P<0.00001), partial remission (OR=1.56, 95%CI: 1.14–2.14, P=0.006), and object response (OR=4.47, 95% CI: 3.02–6.60, P<0.00001) rates in the rAd-p53 combination therapy group compared to those in the CT/RT/CRT group. The results of subgroup analyses of CT/RT/CRT were consistent with the overall results. Regarding the incidence of adverse reactions, only the occurrence rate of fever (OR=18.21,95%CI: 10.54–31.47, P<0.00001) in the rAd-p53 combination group was higher than that in the CT/RT/CRT group. No other significant differences were observed in other adverse reactions. Conclusion: RAd-p53 combined with CT/RT/CRT for the treatment of cervical cancer showed significant advantages in efficacy and safety compared to those in the CT/RT/CRT group. Therefore, rAd-p53 has great potential as an effective therapy for cervical cancer.